Antioxidant activity of melon fruit peel extracts / Sarini Ahmad Wakid and Hamira Azrin Harun - Ahmad Wakid, Sarini; Harun, Hamira Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2020)
The present study was conducted to evaluate the antioxidant activity of peel extract from three types of melon, Cucumis melo var cantalupensis, Cucumis melo var inodorus and Citrullus lanatus in family Curcurbitaceae. The extract was prepared with methanol respectively. 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay were used to study their antioxidant activity. The extracts were compared with commercial antioxidant, butylated hydroxytoluene (BHT). The highest scavenging effect from peel extract was presented by Cucumis melo var inodorus with the value of 52.7 ± 9.1μg/ml (IC50 = 4.61). BHT showed the lowest IC50 value 1.71 with the scavenging activity 90.0 ± 1.7μg/ml. Low IC50 value will indicates the strong ability of the extracts to act as DPPH scavenger.